Korean skilled workers : toward a labor aristocracy - Kim, Hyung-A, 1948- (Korean studies of the Henry M. Jackson School of International Studies., 2020)
"Korean Skilled Workers is the first book to systematically examine the sociopolitical trajectory of South Korea's skilled workers in heavy and chemical industries (HCI). Following the commencement of the Park Chung Hee regime's HCI project in 1972, the Great Workers' Struggle of 1987, and subsequent union militancy, a "labor aristocracy" evolved. In contrast to the uncertain situation of millions of nonregular workers in South Korea today, regular workers achieved guaranteed job security, superior wages, and other benefits. Research on Korean workers has focused on their struggle against political oppression, economic exploitation, and cultural prejudice. In contrast, this study demonstrates that the most enduring struggle of Korea's industrial workers was for wage increases and stable employment, not for a wider revolutionary socialist movement. Korean Skilled Workers draws on archival records and in-depth interviews of HCI workers of three main heavy manufacturing firms (including Hyundai Heavy Industry) to portray these individuals and their vastly changed collective trajectory, showing how their paths embody the consequences of Korea's rapid development, such as the shift from state-led to chaebŏl-led capital accumulation and the limits of a broad-based labor solidarity in the context of a counter-offensive against the strength of the radical unionism of the 1980s"--